Bibliometric and visual analysis of global research: Hospital inpatient satisfaction - Sapto Rini; Kusbaryanto Kusbaryanto; Qurratul Aini (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Background: Patient satisfaction is a crucial metric and the major yardstick for assessing the quality of healthcare delivery. This study aims to investigate the research trends in inpatient satisfaction in hospitals from 2017 to 2022. Materials and Methods: This qualitative study employed a literature review approach. The Scopus search engine was used to identify relevant studies, and VOS viewer was utilized for mapping, while bibliometric analysis was conducted to analyze the data. Results: A total of 137 publications were identified from 2017 to 2021, with 2021 having the highest number of research publications. The largest subject area was medicine, followed by nursing and social sciences. The leading publication source was Patient Preference and Adherence. The United States contributed the most to research publications, and the most prolific author was Liu.Y. The Chinese Academy of Medical Sciences had the highest affiliation with the publications. Conclusion: This bibliometric analysis presents an overview of research on inpatient satisfaction in hospitals from 2017 to 2022, providing valuable insights and guidance for scholars conducting further research. Health Personnel, Hospital Patient Surveys, Patient Satisfaction, Health Care Quality, and Data emerged as the main themes in this bibliometric analysis.